2004
DOI: 10.1007/bf02914569
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal transportation: the effects of a national neonatal transportation programme

Abstract: The National Neonatal Transport Programme has resulted in improved clinical condition of newborns at the end of transfer when compared to their condition before transfer and compared to outcomes prior to the introduction of the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 9 publications
2
4
0
3
Order By: Relevance
“…This was well demonstrated in the subgroup of infants with critical heart defects who received PGE infusion. Improved clinical condition of newborns at the end of transfer has also been found in other studies [6,7].…”
Section: Clinical and Laboratory Resultssupporting
confidence: 79%
“…This was well demonstrated in the subgroup of infants with critical heart defects who received PGE infusion. Improved clinical condition of newborns at the end of transfer has also been found in other studies [6,7].…”
Section: Clinical and Laboratory Resultssupporting
confidence: 79%
“…L'hypothermie était présente chez presque tous les nouveau-nés transférés dans l'étude malienne et chez 47 % en Inde [11,13]. En Irlande, les cas d'hypothermie (7 %) et d'hypoglycémie (3 %) étaient beaucoup plus rares à l'admission [5]. Certains nouveau-nés avaient nécessité des mesures de réanimation lourdes, qui ne pouvaient pas être assurées correctement dans tous les centres.…”
Section: éTat à L'arrivéeunclassified
“…Ces différentes situations de détresse néonatale nécessitent très souvent un transfert des structures de naissance, souvent situées en zones périphériques, peu dotées en personnels qualifiés et en plateaux techniques adaptés, vers des services de néonatologie de référence. La bonne organisation de ces transferts représente l'une des conditions essentielles pour réduire la morbidité et la mortalité néonatales [4,5]. Plusieurs préalables sont nécessaires : une définition claire des indications de transfert en fonction du niveau de soins ; un personnel périphérique entraîné à la réanimation et aux soins néo-natals ; des moyens de transport équipés et adaptés aux nouveau-nés et une parfaite coordination entre les différentes structures impliquées et la famille [6].…”
Section: Introductionunclassified
“…Mullane et al, [5] before transport found 17% of neonates to be hypothermic, 2% hypoglycemic and 11% acidotic as compared to 7%, 3% and 5%, respectively at the end of transfer. In the present study, significant improvement in temperature, blood pressure, oxygen saturations and blood sugars was found in the babies as compared to their status at the referring hospital ( Table 1).…”
Section: Discussionmentioning
confidence: 95%